2016
DOI: 10.1104/pp.16.01212
|View full text |Cite
|
Sign up to set email alerts
|

Phloem Transport of the Receptor DWARF14 Protein Is Required for Full Function of Strigolactones

Abstract: The cell-to-cell transport of signaling molecules is essential for multicellular organisms to coordinate the action of their cells. Recent studies identified DWARF14 (D14) as a receptor of strigolactones (SLs), molecules that act as plant hormones and inhibit shoot branching. Here, we demonstrate that RAMOSUS3, a pea ortholog of D14, works as a graft-transmissible signal to suppress shoot branching. In addition, we show that D14 protein is contained in phloem sap and transported through the phloem to axillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…DR14 protein could work as an intercellular signaling molecule to fine-tune SL function (Kameoka et al, 2016). Recently, a hypothesis in which SL may indirectly influence seed size has been created.…”
Section: Discussionmentioning
confidence: 99%
“…DR14 protein could work as an intercellular signaling molecule to fine-tune SL function (Kameoka et al, 2016). Recently, a hypothesis in which SL may indirectly influence seed size has been created.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for SL because shoot branching is a complicated process involving local and systemic decisions. SL signaling genes are expressed in the buds as well as in vascular bundles, consistent with the two modes of SL function in which SL regulates the PATS and downstream transcription cascades (Stirnberg et al ., ; Zhou et al ., ; Chevalier et al ., ; Soundappan et al ., ; Kameoka et al ., ; Liang et al ., ). However, more precise identification of the site of SL function is required to better understand the mechanisms by which SL inhibits bud outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that DWARF14 (D14), a receptor of strigolactone (SL) hormone in rice, is transported long distances through phloem and then moves into axillary meristems (AMs) to regulate the function of SLs in the development of AMs [40]. D14 mRNA accumulates in vascular bundles and leaf primordia, whereas natively expressed GFP-fused D14 protein (D14-GFP) can be found in AMs, suggesting that it is mobile.…”
Section: Macromolecular Trafficking Through Pd In the Sammentioning
confidence: 99%